INTEGRASI CENTRAL AUTHENTICATION SERVICE (CAS) DENGAN FREERADIUS SEBAGAI SINGLE-SIGN-ON - suryadi, irvan (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
The evolution of information technology has made lots of organizations use web-based applications to improve their work performance. Using two or more web-based applications in an organization makes users have to remember more than one account to log in to the websites. This is certainly ineffective, and it takes technology that can make users to access all existing web applications using one account. The technology commonly used is the Single-Sign-On (SSO) technology. In this study, the Single-Sign-On protocol that was developed was the Central Authentication Service or CAS. To implement a centralized authentication system, FreeRADIUS is used as an authentication server and authentication protocol. To make both technologies work, this study will explain how to integrate SSO with CAS protocol as SSO and FreeRADIUS as authentication server, to create SSO based on CAS and FreeRADIUS. Success is determined in the login and logout process. After the user has logged into the SSO portal, the user can access all existing web applications. Keywords - Central Authentication Service (CAS), FreeRADIUS, Single-Sign-On (SSO).